Blood flow restriction training for the shoulder: A case for proximal benefit - Lambert, B.; Hedt, C.; Daum, J.; Taft, C.; Chaliki, K.; Epner, E.; McCulloch, P. (The American Journal of Sports Medicine, 2021)
Background: Although blood flow restriction (BFR) is becoming increasingly popular in physical therapy and athletic training settings, little is known about the effects of BFR combined with low-intensity exercise (LIX) on muscles proximal to the site of occlusion.